Esculetin and Fucoidan Attenuate Autophagy and Apoptosis Induced by Zinc Oxide Nanoparticles through Modulating Reactive Astrocyte and Proinflammatory Cytokines in the Rat Brain - Woo-Ju Song; Jeongtae Kim; Taekyun Shin; Myeong-Seon Jeong; Kil-Nam Kim; Jang-Hyuk Yun; Myung-Bok Wie (Toxics, 2022)
We examined the protective effects of esculetin and fucoidan against the neurotoxicity of ZnO NPs in rats. Ninety rats were divided into nine groups and pre-treated with esculetin or fucoidan 1 h before ZnO NP administration on a daily basis for 2 weeks. Serum and brain homogenates were examined by enzyme-linked immunosorbent assay (ELISA), and neurons, microglia, and astrocytes in the hippocampal region were examined with immunohistochemical analysis. The serum levels of interleukin-1-beta (IL-1β), 3-nitrotyrosine (3-NT), superoxide dismutase (SOD), and 8-hydroxy-2′-deoxyguanosine (8-OHdG) were altered in the ZnO NP treatment groups. Brain IL-1β and TNF-α levels were elevated after ZnO NP administration, and these effects were inhibited by esculetin and fucoidan. SOD, 8-OHdG, and acetylcholinesterase (AChE) levels in the brain were decreased after ZnO NP administration. The brain levels of beclin-1 and caspase-3 were elevated after ZnO NP treatment, and these effects were significantly ameliorated by esculetin and fucoidan. The number of reactive astrocytes measured by counting glial fibrillary acidic protein (GFAP)-positive cells, but not microglia, increased following ZnO NP treatment, and esculetin and fucoidan ameliorated the changes. Esculetin and fucoidan may be beneficial for preventing ZnO NP-mediated autophagy and apoptosis by the modulation of reactive astrocyte and proinflammatory cytokines in the rat brain.